Candidate gene studies in hypodontia suggest role for FGF3 - Vieira, Alexandre Rezende; D'Souza, Rena; Mues, Gabriele; Deeley, Kathleen; Hsin, Hongyuan; Küchler, Erika Calvano; Meira, Raquel; Patır, Aslı; Tannure, Patrícia Nivoloni; Lips, Andrea; Meneghim, Marcelo de Castro; Granjeiro, José Mauro; et al. (My University, 2013)
Introduction The majority of tooth agenesis cases are mild (hypodontia) and typically not associated with the gene mutations linked to oligodontia. From this, we hypothesise that most cases of tooth agenesis fit a polygenic mode of inheritance, where several genes with small effects cause a variety of varying phenotypes. Materials and methods In this study, we looked at 18 not typically studied genes in this condition, to ascertain their contribution to hypodontia. Our study subjects consisted of 167 patients with hypodontia and their parents from two cohorts (one from Brazil and one from Turkey). An additional 465 DNA samples (93 cases with hypodontia and 372 controls without family history for tooth agenesis or oral clefts) from Brazil were also available for this study. Ninety-three single nucleotide polymorphisms that maximally represent the linkage disequilibrium structure of the genes for the 18 genes were selected and genotyped using Taqman chemistry. Chi square was used to test if genotype distributions were in Hardy–Weinberg equilibrium, and 24 markers that were in Hardy–Weinberg equilibrium and had allele frequencies higher than 5 % in a panel of 50 CEPH samples were further tested. Association between hypodontia and genetic variants was tested with the transmission disequilibrium test within the programme Family-Based Association Test (FBAT) and by using Chi square and Fisher’s exact tests. Alpha at a level of 0.05 was used to report results.
Keywords: Tooth Abnormalities; Odontogenesis; MSX1; PAX9; PITX2